Adaptive Potential of the Heme Oxygenase/Carbon Monoxide Pathway During Hypoxia - Tift, Michael S.; Alves de Souza, Rodrigo W.; Weber, Janick; Heinrich, Erica C.; Villafuerte, Francisco C.; Malhotra, Atul; Otterbein, Leo E.; Simonson, Tatum S. (Frontiers in Physiology, 2020)
Heme oxygenase (HO) enzymes catalyze heme into biliverdin, releasing carbon monoxide (CO) and iron into circulation. These byproducts of heme degradation can have potent cytoprotective effects in the face of stressors such as hypoxia and ischemia-reperfusion events. The potential for exogenous use of CO as a therapeutic agent has received increasing attention throughout the past few decades. Further, HO and CO are noted as putatively adaptive in diving mammals and certain high-altitude human populations that are frequently exposed to hypoxia and/or ischemia-reperfusion events, suggesting HO and endogenous CO afford an evolutionary advantage for hypoxia-tolerance and are critical in cell survival and injury avoidance. Our goal is to describe the importance of examining HO and CO in several systems, the physiological links, and the genetic factors that underlie variation in the HO/CO pathway. Finally, we emphasize the ways in which evolutionary perspectives may enhance our understanding of the HO/CO pathway in the context of diverse clinical settings.